Desenvolvimento da leitura nos anos iniciais do ensino fundamental : letramento através do poema - Silva, Valdineide Moreira da (2023)
Reading is a social need and its practice in the classroom, in addition to being indispensable, requires a closer look, especially in childhood, so that the child's reading skills can actually be developed. This work addresses discussions about the need to practice reading in the classroom, literary literacy and its role in the development of reading in childhood, as well as the importance of literary texts in this process, with emphasis on the poem genre. It also presents a work proposal in which reading practices are developed from the literary genre poem. The methodology used is based on the fundamentals of literary literacy, planned through a ludic sequence of reading that was performed in Portuguese Language classes in a 5th grade class of Elementary School in a public school. Among the theoretical bases that support this research, the studies by Bordini (1986), Coelho (2000), Cosson (2021), Kleiman (2016), Lyra (1986), Miguez (2009) and Pinheiro (2018) stand out. The children involved in this research felt encouraged to read and improve their reading ability through the playfulness and enchantment that the poem genre provides.